Kajian Historis terhadap Perkembangan Resolusi Konflik Etnis dan Agama di Bosnia-Herzegovina - Pratama, Fikri Surya (JSI: Jurnal Sejarah Islam, 2023)
Politically and geographically, Bosnia is often a victim of the Western political divisive propaganda and extremist Islamic movements. This has left Bosnia and Herzegovina embroiled in ethnic and religious conflicts between Bosnians, Serbs and Croats for decades. This journal article explores the history of ethno-religious conflict in Bosnia, and how the government has created a peaceful, multi-ethnic and religious European Muslim nation amid radical siege of "propaganda". It is intended to explain how Movement and Western Politics. This research is a historical study using a data collection method called literature survey. The main sources are magazine articles and YouTube channels interviewing living witnesses to the Bosnian conflict and contemporary Bosnians. Sources have been criticized for their objectivity, particularly in filtering Western "opinions," analyzed with a political-historical approach, and finally concluded at the stage of historiography. Findings show that post-peace Bosnia has failed to declare itself an Islamic state, with politics used by irresponsible political parties to provoke decades of ethnic and religious conflict in Bosnia. ``Three M'' ideology: Multicultural. multi-ethnic; became a rallying cry to unite modern-day Bosnia in the face of its grappling with collapse. All religious adherents are free to practice their faith, and each of the three major ethnic languages has been declared the official language of the country